In a surveillance and regulation of protest movements in a democratic liberal society: exploring the lives of Fees Must Fall activists at Stellenbosch University. - Phillips, Ashwin Lorenzo (Stellenbosch : Stellenbosch University, 2021)
Thesis (MA)--Stellenbosch University, 2021.